SHARIA COMPLIANCE : CONSUMER PERSPECTIVE IN E-COMMERCE PRACTICES - Muhammad Ilyas Candra Herawan; Juliana Juliana; Arim Nasim; Firmansyah Firmansyah (STIESA Press, 2022)
This research is backed by the rapid development of technology that makes it easier for people to do buying and selling activities. People can easily choose goods and transact only with smartphones that are connected to the Internet. But from the facilities offered, online trading is not separated from violations that are not in accordance with the principles of the rulings in Islam such as fraud, inconsistency of goods, inconsistency of the receipt of goods, and Mismatch between price and quality. The purpose of this study is to know and describe the implementation of sharia compliance in the perspective of consumers among students of the University of Indonesia education. As for the method used in this research is quantitative descriptive, the population is a student of Indonesian University of Education, research using sample 100 respondents representing every faculty in the university Indonesian education, with sampling techniques in a non-probabillity sampling manner. Based on the research done, it is known that consumer understanding among UPI students belongs to the good category, judging by the online buying and selling literature with the pillars and the terms of buying and selling greetings. This research has important implications for online buying and selling people, because Islam has arranged all human activities and online buying and selling including them. So, in practice online buying and selling is not only profit for the seller and ease of transaction for both parties, but also to get the blessing and reward of buying and selling activities in accordance with the principles of Islamic rules.